ENTERPRISE ARCHITECTURE UNTUK INDUSTRI KONSTRUKSI INDONESIA - Budi Setyawan (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Enterprise Architecture is closely related to the meaning of integration from various fields within a company, it is also a description of business, information, applications, and technology in the development of a framework or set of frameworks. Enterprise Architecture can identify strategies and provide information to balance business with technology, it is also useful for the management of a company because it can improve the implementation or execution of activities in various fields. With Enterprise Architecture, risks can be reduced or reduced, and business strategies can be more harmonious. To develop an idea, of course it must be described first. After being able to describe, then can be developed. Enterprise Architecture describes as a whole and a broad scope, in addition to being broad it must also be complete, covering all aspects. After the company or organization is described in full, then it enters the management stage, how to properly manage existing resources, and think about how to procure resources that do not yet exist, but are needed. The next process is development, such as Business Architecture, Application Architecture, Information Architecture, Technology Architecture. All described and managed, a healthy company or organization is one that develops with the concept of growing houses